The Volcanic Rocks of Poonch District, Azad Kashmir - Chaudhry, Muhammad Nawaz; Ashraf, Mohammad (Journal of Himalayan Earth Sciences, 1980)
The volcanic rocks of the Poonch District are confined to the Pir Panjal Range of Upper Haveli, Poonch District. The volcanic rocks belong to two distinct ages. The Dogra Trap is basaltic and is confined within the Precambrian Dogra Slates. The Panjal Trap along with basal agglomeratic slates and Tuffs are Upper Carboniferous. The flows are mainly basaltic to andesitic. The pyroclasts occurring towards the top are intermediate to acidic in composition. The Panjal Trap is overlain by the ’Gondwana Group’ of upper part of Upper Carboniferous to Permian. This paper deals with the geology, petrography, chemistry and geochemistry of the Poonch volcanics. Map of the area on 1:50000 has been prepared. This is the first detailed petrological study of the Poonch Volcanics. A total of thirty nine petrographic analyses, thirty two chemical analyses and fifteen spectro- chemical analysis of the volcanics are presented.